Investigation into possibility of rejuvenating aged asphalt binder using mustard oil. Issue 6 (12th May 2022) - Ahmad, Tufail; Ahmad, Naveed; Jamal, Muhammad; Badin, Gul; Suleman, Muhammad
ABSTRACT: Incorporation of high content of Reclaimed Asphalt Pavement (RAP) into fresh asphalt mixtures make them prone to thermal cracking and fatigue failure. Rejuvenators are usually recommended to overcome this problem by restoring the aged asphalt binder properties. This study aims to investigate the feasibility of using Mustard oil as a rejuvenator and to evaluate its effectiveness as a rejuvenator by determining the extent to which it restores the chemical and physical properties of aged asphalt binder extracted from RAP. The effect of Mustard oil on physical, rheological, chemical and thermal properties of aged asphalt binder was studied by employing Rotational Viscometer, Dynamic Shear Rheometer, Bending Beam Rheometer, Fourier Transform Infrared Spectroscopy, Thermogravimetric analysis, Gas-Chromatography-Mass Spectrometry and Rolling bottle equipment. Results indicated that Mustard oil effectively restores the properties of aged asphalt binder and can be used as a suitable rejuvenator. Ten per cent of Mustard oil is recommended as an optimum dose for rejuvenation of aged asphalt binder. This dose is based on restoring the RAP binder to match the properties of neat binder having PG64 and is specific to the stiffness of RAP material being used.